Maternal mental health and substance use disorders in sudden unexpected death in infancy using routinely collected health data in New Zealand, 2000–2016. Issue 10 (8th June 2022) - Mitchell, Edwin A; Zhang, Doney; Thompson, John M D; Liu, Chris; Leversha, Alison; Milne, Barry J
Abstract : Background: Mortality from sudden unexpected death in infancy (SUDI) has declined dramatically since the 'Back to Sleep' campaign. Deaths now are more prevalent in those with socioeconomic disadvantage. The investigation of SUDI frequently identifies parents that have mental health or drug, alcohol and addiction problems. Aims: To estimate the prevalence of maternal mental health and substance use disorders and assess the magnitude of their risk for SUDI. Methods: We conducted a population-based cohort study using data from the Integrated Data Infrastructure (IDI), a large research database containing linked data from a range of government agencies. The study population was all live births and their mothers in New Zealand from 2000 to 2016. The exposures of interest were maternal mental health problems and maternal substance use disorders in the year prior to the birth. The outcome was deaths from SUDI. Results: The total population was 1086 504 live births and of these 1078 811 (99.3%) were able to be linked to other data sets within the IDI. The prevalence of maternal mental health problems in the total population was 5.2% and substance use disorder was 0.7%. There were 42 deaths from SUDI (0.75/1000) that were exposed to maternal mental illness and 864 deaths (0.84/1000) that were not exposed (adjusted relative risk (aRR)=1.23, 95% CI 0.90 to 1.68). There were 21 deaths from SUDI (2.67/1000) that were exposed to maternal substance use disorders and 885 (0.83/1000) that were not exposed (aRR=1.82, 95% CI 1.17 to 2.83). Conclusions: Maternal substance use disorders, but not maternal mental health problems, in the year prior to the child's birth was associated with an increased risk of SUDI. However, the numbers that are affected are small and the effect size moderate. This group of women should receive additional SUDI prevention services and Safe Sleep advice. Abstract : This population-based cohort study of live births in New Zealand using health administrative data showed maternal substance use disorders but not maternal mental health problems in the year prior to an infants birth was associate with a moderately increased risk of sudden unexplained death of infancy.